Modelagem Matemática da Intercalação de Fragmentos Aromáticos Sobre o Silicone por Meio da Eletrorredução de Diazocompostos Correspondentes - Tkach, Volodymyr Valentynovych; Cherkaoui, Mohammed; Ojani, Reza; Yagodynets´, Petro (Orbital: The Electronic Journal of Chemistry, 2016)
The mathematical model, describing the intercalation of aromatic fragments to the silicone surface by means of electrochemical reduction of respective diazo-salts, was represented and analyzed, by linear stability theory and bifurcation analysis.  A theoretic comparation of the behavior of this system with that of analogous system was also made by modeling.DOI: http://dx.doi.org/10.17807/orbital.v8i3.805